Planejamento de colheita de madeira em região montanhosa com uso de modelagem espacial e programação linear inteira - Rudek, Alynne (2014)
Given the difficulties encountered in the realization of forest harvesting in mountainous areas, this paper aims to define the planning of timber harvesting in mountainous region with the support of computational tools. From the collected data relating to the extraction and processing of timber operations using cable logging, a mathematical model was developed to predicting the allocation of towers to harvest using cable logging, which included the variables system productivity, distance extraction, timber volume per cell (100 m²), land slope and time operating cycle. With this model it was possible to simulate the allocation of the towers under different conditions, and therefore, the system performance considering different variables influence on the system, which allows taking more assertive decisions about the allocation of the towers and system planning. This work was performed in the operational areas of forest harvesting, belonging to the company Berneck. Using ArcGIS tools mapping of existing classes of slope was conducted in the study area, and using the slope as a criterion for determining the most appropriate systems for logging, areas were defined to be harvested using different extraction systems applied by the company. Were used as tools for planning of forest harvest Operations Research and Geographical Information Systems. The results showed that a large portion of the study area showed high slopes, belonging classes 15° to 20° and 21° to 30°, corresponding to 28,51% and 54,85% of the total area, respectively, then being performed in these areas wood harvesting system using cable logging. The cable logging represented 91,01% of the areas to be harvested using this system. The class of distance equivalent to 200 m extraction accounted for 57,43% of the total area to be harvested with the cable logging system, followed by the distance 201-400 m with 26,86% of the total area, while other areas were found in classes with values greater than 400 m. For the scenario of minimizing the sum of the distances of extraction, the model estimated the productivity of the system under different slope and distance extraction conditions. It was found that the productivity of the system ranged between 21,0 m³ h-1 and 18,0 m³ h-1 in the distance classes of 50 m and 150 m, respectively. For the range of slope equal to 7° and 45°, the productivity ranged between 21,0 m³ h-1 and 17,27 m³ h-1 respectively, for the same scenario. As the scenario for minimizing the cycle time operating the system productivity ranged from 21,68 m³ h-1 16,0 m³ h-1 , in the range of distance equal to 100 m and 200 m, respectively. By varying the slope between 5° and 20°, the productivity ranged between 20,57 m³ h-1 and 18,86 m³ h-1 respectively. The results showed that the variable "Cycle Time" affects the definition of the points allocation towers, resulting in fewer positions to be occupied by the tower and consequently larger area of extraction tower; the variable "Distance Extraction" affects the definition of the points allocation tower, resulting in the selection of more locations for installation of the towers, thus resulting in greater movement of the towers. The model developed for allocation of towers is efficient, but needs to be improved to ensure greater precision in cases where the extraction is performed over long distances. This information helps in decision making in the planning stage of the harvesting operation with cable logging.